P047 HISTOLOGICAL AND ENDOSCOPIC HEALING AFTER QBECO TREATMENT IN AN OPEN-LABEL PHASE 2 STUDY IN PATIENTS WITH ULCERATIVE COLITIS. (18th January 2018) - Pankovich, Jim; Kalyan, Shirin; Bazett, Mark; Sham, Ho Pan; Fedorak, Richard N; Marshall, John K; Bressler, Brian; Sutcliffe, Simon; Gunn, Hal
Abstract: Introduction: Current therapies for inflammatory bowel disease (IBD) are aimed at immune suppression. These have not prevented disease progression for the majority of IBD patients and come with consequent risk. There is a recognized need for new, safe and effective treatment for IBD. QBECO is a novel microbial-based immunotherapy designed to stimulate the immune response to overcome immune dysfunction in the gastrointestinal tract. QBECO has previously shown promising results in a randomized double-blind placebo controlled phase 2 clinical trials in Crohn's disease (CD; NCT01809275). These findings were followed-up with a phase 2 open-label trial in ulcerative colitis (UC) to assess endoscopic and histological improvement (NCT02426372). Methods: An open-label phase 2 trial was conducted with 11 patients with moderate-to-severe UC. QBECO was self-administered subcutaneously every second day throughout the 16 weeks. Endoscopic and histological assessment was measured at screening, week 8 and week 16. QBECO responders were defined as having a decrease in Mayo score (composite of endoscopic healing, rectal bleeding, stool frequency and global physician's assessment) of 3 or more points. Results: 7 of 11 patients (63.6%) responded to QBECO and 1 patient (9.1%) was in clinical remission by week 16. For the individual Mayo sub scores, at least a one point improvement was seen in 63.4% of patients for stool frequency, 81.8% for rectal bleeding, 60.0% for endoscopic improvement and 54.5% of patients for global physician's assessment. Histological improvement was seen in 5 of 10 patients (50%) that had week 16 histology samples. Conclusion: In this proof-of-concept study, UC patients experienced clinical, endoscopic and histological improvement after 16 weeks of QBECO treatment. This highlights the potential for this novel microbial-based immunotherapeutic strategy to restore gastrointestinal immune function in patients with UC.